NON INVASIVE DIAGNOSIS AND ASSESSMENT OF THE SEVERITY OF PULMONARY HYPERTENSION IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE - Ali, Kosar M.; Omer, Shirwan H.; Abdalla, Razhan Y. (Journal of Sulaimani Medical College, 2019)
Background Pulmonary hypertension (PH) is a common complication of advanced chronic obstructive pulmonary disease (COPD) and is defined by a mean pulmonary artery pressure (PAP) ≥ 25 mm Hg, Pulmonary vascular remodeling in COPD is the main cause of increase in pulmonary artery pressure and is thought to result from the combined effects of hypoxia, inflammation and loss of capillaries in severe emphysema. There is a paucity of worldwide data on prevalence and incidence of PH in COPD. There are also wide variations in the reported prevalence rates in the few studies that have been carried out. This is largely due to the definition of PH and the method of measurement of PAPs. The diagnosis of PH relies on Doppler echocardiography, and right heart catheterization is needed in a minority of patients. Objectives This cross-sectional study involved 60 patients with COPD. The entire subjects met certain inclusion and exclusion criteria to exclude other possible contributing factors of pulmonary hypertension. All subjects completed a questionnaire, after clinical examination and investigations, the diagnosis of COPD made by a Specialist Physicians in the hospital and Echocardiography was performed by a cardiologist. Results The mean age of included patients was 67.1±11.2 years; males were more than females with male to female ratio as 2.75:1, among study sample (48.4%) COPD patients were current smokers, with mean of 54±29 packs/year, mean Spo2 of COPD patients was 89.7±6 %. The Gold staging of COPD patients was distributed as followings; stage I (25%), stage II (33.3%), stage III (21.7%) and stage IV (20%), Pulmonary hypertension (PH) as diagnosed by echocardiography was present among 66.7% of COPD patients. Prevalence of pulmonary hypertension among COPD patients in our study was 66.7%. And pulmonary hypertension severity was distributed as followings; mild (37.5%), moderate (32.5%) and severe (30%). Right ventricular hypertrophy was present among 31.7% of COPD patients. Conclusion High incidence of pulmonary hypertension among patients with chronic obstructive pulmonary diseases, pulmonary hypertension severity is related with the severity of chronic obstructive pulmonary diseases and Echocardiography is useful and effective tool for detection of pulmonary hypertension secondary to chronic obstructive pulmonary disease.
Keywords: Chronic Obstructive pulmonary disease; Pulmonary Hypertension; Echocardiography